Preoperative β‐blockade and hypertension in the first hour of functional endoscopic sinus surgery. (3rd February 2017) - Schechtman, Samuel A.; Wertz, Aileen P.; Shanks, Amy; Thompson, Aleda; Tremper, Kevin; Pynnonen, Melissa A.; Healy, David W.
Abstract : Objectives/Hypothesis: Local anesthetic with epinephrine is commonly injected into the nasal mucosa during functional endoscopic sinus surgery (FESS). Systemic absorption of epinephrine following local injection may occur, resulting in a mild sympathetic response. This study seeks to determine whether an exaggerated sympathetic response to epinephrine is demonstrated in patients undergoing FESS treated preoperatively with established pharmacologic beta (β) adrenoceptor blockade. Study Design: A retrospective analysis of adult patients undergoing FESS at a tertiary care university hospital. Methods: The primary outcome was the occurrence of an exaggerated hypertensive response within the first hour of surgical time defined by a relative increase (>20%) in the first measured intraoperative systolic blood pressure (SBP) prior to induction of anesthesia, or a single SBP value above 200 mm Hg. A mixed effects logistic regression model was developed to identify independent predictors of an exaggerated hypertensive response and describe the variance in the outcome attributable to the surgeon and anesthesiologist. Results: There were 2, 051 patients identified. Independent predictors of an exaggerated intraoperative hypertensive event included: preoperative β‐blocker use (adjusted odds ratio [AOR]: 3.33), female gender (AOR: 1.92), body mass index (AOR: 1.03), lower baseline SBP (AOR: 0.93), and advanced age (AOR: 1.03). The C statistic for the model was 0.8881. Conclusions: Preoperative β‐blocker use is an independent predictor of an exaggerated hypertensive response within the first hour of operative time. An exaggerated hypertensive effect should be anticipated in patients presenting for FESS with established pharmacologic β‐blockade, and caution should be applied to use of epinephrine‐containing solutions. Level of Evidence: 4. Laryngoscope, 127:1496–1505, 2017